The Use of Teaching Proficiency through Reading and Storytelling (TPRS) to Promote Vocabulary Learning Achievement of Fourth-Grade Students - Ponguagoon, Paktada; Lornklang, Thanachart (Ratchaphruek Journal, 2022)
The research objectives of this study were: 1) to investigate the effects of Teaching Proficiency through Reading and Storytelling (TPRS) on students’ vocabulary learning achievement, and 2) to examine students’ opinions towards learning English using Teaching Proficiency through Reading and Storytelling (TPRS). The population was fourth-grade students from 4 government schools, and the samples were 13 fourth-grade students at Ban Nongrung School, Khonburi District, Nakhon Ratchasima Province. They were selected by using cluster random sampling. The instruments were the three lesson plans based on the TPRS, an English vocabulary learning achievement test, and a questionnaire. The data were analyzed using mean ( ), standard deviations (S.D.), percentage, and t-test for a dependent sample. The results of this research showed that the mean score of the post-test of the English vocabulary learning achievement of the participants who learned English using Teaching Proficiency through Reading and Storytelling (TPRS) was significantly higher than the pre-test one at the .05 level of statistical significance. The participants had favorable opinions about learning English using Teaching Proficiency through Reading and Storytelling (TPRS). This study indicated that using Teaching Proficiency through TPRS could effectively improve fourth-grade students’ vocabulary learning achievement.